The appraisal of sustainable materials - Bin,Bahrudin FI; Aurisicchio,M (Design Society, 2018)
This paper seeks to understand how users appraise and perceive sustainable materials. Using thinking aloud sessions, appraisals of sustainable materials embodied in commercial products were collected from users and categorised. To account for the appraisalof systemic features of materials we have extended a previous categorisation ofmaterial appraisals. We have also investigated the relationships between the appraisal themes of sustainable materials. The results stress the influence of material origin in the appraisal.This understanding is useful to facilitate the uptake of the materials.